Alginate-based strategies for therapeutic vascularization. (March 2013) - Gandhi, Jarel K; Opara, Emmanuel C; Brey, Eric M
Therapeutic stimulation of vessel growth to improve tissue perfusion has shown promise in many regenerative medicine and tissue engineering applications. Alginate-based biomaterial systems have been investigated for growth factor and/or cell delivery as tools for modulating vessel assembly. Growth factor encapsulation allows for a sustained release of protein and protection from degradation. Implantation of growth factor-loaded alginate constructs typically shows an increase in capillary density but without vascular stabilization. Delivery of multiple factors may improve these outcomes. Cell delivery approaches focus on stimulating vascularization either via cell release of soluble factors, cell proliferation and incorporation into new vessels or alginate prevascularization prior to implantation. These methods have shown some promise but routine clinical application has not been achieved. In this review, current research on the application of alginate for therapeutic neovascularization is presented, shortcomings are addressed and the future direction of these systems discussed.